Hip Hop Battles and Facial Interexts - Dodds, Sherril 1967- (Edinburgh: Edinburgh University Press, 2016)
RESUMEN: Hip hop dance battles are organized around a face-to-face danced exchange and, although dancers mobilize a diverse range of facial expression, scarcely any scholarly work addresses the face as a choreographic device. Several scholars, however, have noted that hip hip battles are dialogic or conversational in style, and I assert that dancers strategically employ facial expression to challenge and comment upon their opponents. In this article, I draw on the theory of intertextuality, and in particular Henry Louis Gate's concept of signifyin(g), to show how dancers deploy facial choreography as a mode of embodied articulation. Based on an ethnography of hip hop battles in Philadelphia, I examine the choreography of facial expression in four particular ways: as a strategy to signal generic particularity; to make commentary on the actions of other body parts; to create dialogic exchange between other faces at the battle event; and to reference facial intertexts from the broader popular culture. PALABRAS CLAVE: hip hop, facial expression, intertextuality, genre, signifyin(g)